Studies on mononuclear chelates derived from substituted Schiff base ligands (Part 4): Synthesis and characterization of a new 5-hydroxysalicyliden-P-aminoacetophenoneoxime and its complexes with Co(II), Ni(II), Cu(II) and Zn(II) - Canpolat, E; Kaya, M (Tubitak Scientific & Technological Research Council Turkey, 2005)
5-Hydroxysalicyliden-graminoacetophenoneoxime (LH) was synthesized starting from p-aminoacetophenoneoxime and 5-hydroxysalicylaldehyde. Complexes of this ligand with Co+2, Ni+2, Cu+2 and Zn+2 salts were prepared. With this ligand, complexes were synthesized using Co+2, Ni+2, Cu+2 and Zn+2 salt with a metalaigand ratio of 1:2. Their structures were elucidated on the basis of elemental analyses, IR, H-1- and C-13-NMR, electronic spectra, magnetic susceptibility measurements, molar conductivity and thermogravimetric analyses.
Keywords: Schiff bases; transition metal complexes; oxime